The Effect of Solvency, Audit Committee, Reputation of Public Accounting Firms, and Audit Opinions on Audit Delay : Empirical Study on Manufacturing Companies in Various Industrial Sectors Listed on The Indonesia Stock Exchange for The Period 2017–2021 - Marwaziyyah, Nur Izzah; Meini, Zumratul; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to analyze what factors affect audit delay in manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The model in this study consists of four independent variables, namely solvency, audit committee, reputation of public accounting firms, and auditor opinion. In addition, this study also used audit delay as a dependent variable. The secondary data used in this study is in the form of financial statements and audit reports from manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange (IDX) in 2017-2021. With a sample number of 100 companies. The sample selection is based on three criteria: (1) Companies listed on the IDX in the 2017-2021 period and consistently publish financial statements. (2) Financial statements shall be presented in rupiah currency and shall expire on December 31. (3) Have data related to the variables used in the study. The results of regression testing show that two independent variables, namely the reputation of the public accounting firm and audit opinion negatively affect audit delay. Meanwhile, solvency and the audit committee do not influence audit delay. This means that the high and low solvency ratios do not affect the audit completion period or audit delay. The large proportion of debt owned by the company is reasonable as long as there is adequate disclosure, so it will not hamper the auditor in carrying out his audit work. Also, the increasing number of audit committees will make it difficult to form a good communication and coordination network between audit committee members.